Tracking of anthropometric characteristics from childhood to adolescence: an 8-year follow-up findings from the Czech ELSPAC study - Zvonar, Martin; Štefan, Lovro; Kasović, Mario; Piler, Pavel (BMC public health, 2022)
BACKGROUND: Although evidence suggests that obesity track well from childhood to adolescence, most of the research has been done in Western and high-income countries. Moreover, most of the studies have tracked body-mass index, as a proxy of nutritional status, while tracking characteristics of circumferences and skinfold thicknesses have been less studies. Therefore, the main purpose of the study was to explore tracking characteristics of complete anthropometric data from childhood to adolescence. METHODS: This sub-study was part of the Czech ELSPAC study. In the present 8-year longitudinal study, we collected information from pediatrician's medical records at the ages of 8 y (n = 888), 11 y (n = 1065), 13 y (n = 811) and 15 y (n = 974), including circumferences (head, chest, waist, hips, and arm), indices (body-mass index, waist-to-hip ratio and waist-to-height ratio) and skinfold thicknesses (biceps, triceps, subscapula, suprailiaca, thigh and the sum of 5 skinfolds). Participants were recruited from the two selected regions of the Czech Republic (Brno and Znojmo). Linear generalized estimating equations were conducted to analyze tracking patterns over an 8-year follow-up period for all anthropometric measurements. RESULTS: Tracking coefficients were moderate to strong, ranging from 0.40 to 0.62 for circumferences, 0.41 to 0.74 for indices and 0.72 to 0.86 for skinfolds. According to body-mass index and waist circumference standards, overweight/obese children and children with abdominal obesity at the age of 8 y were 11.31 (95% CI = 8.41 to 15.22, p < 0.001) and 10.73 (95% CI = 7.93 to 14.52, p < 0.001) more likely to remain overweight/obese and to have abdominal obesity at the age of 15 y. CONCLUSIONS: Findings show moderate to strong tracking of anthropometric characteristics, i.e. circumferences track moderately well, while strong tracking for indices and skinfold thicknesses is observed. Moreover, strong tracking of general overweight/obesity and abdominal obesity between ages 8 y and 15 y indicates that the detection of these risk factors at the beginning of primary school should be advocated.
Keywords: index tělesné hmotnosti; Youth; longitudinální studie; Circumferences; Obesity; Stability; tloušťka kožní řasy; Skinfolds; mladiství; Česká republika; Pediatric Obesity; Overweight; Obesity, Abdominal; Czech Republic; Body Mass Index; Follow-Up Studies; dítě; Child; následné studie; Skinfold Thickness; Anthropometry; Humans; antropometrie; nadváha; Longitudinal Studies; abdominální obezita; Indices; Adolescent; obezita dětí a dospívajících; lidé